Efektivitas Kompres Hangat Kering dan Kompres Water Tepid Sponge terhadap Penurunan Suhu Tubuh pada Pasien Anak Demam di Rumah Sakit Islam Pati - Ifrokhah, Yeni; Feri Catur Yuliani; Yeni Rusyani (Pusat Riset dan Inovasi Nasional, 2025)
Background: According to the 2020 Ministry of Health Profile, fever accounts for 7.3% of infant deaths in Indonesia. Fever is a common complaint in children, with 20–40% of parents reporting their child's illness each year. Approximately 19–30% of patients visiting doctors are children, and fever is one of the primary complaints. If not treated promptly, fever can lead to complications such as seizures and decreased consciousness. Fever management can be done through pharmacological (antipyretic, NSAID, diazepam) or non-pharmacological measures, one of which is by applying compresses. Objective: To determine the effectiveness of dry warm compresses and water tepid sponge compresses on reducing body temperature in pediatric patients at Pati Islamic Hospital. Method: Quantitative research with a quasi-experimental two-group pre–post test design using a purposive sampling technique. Results: The application of water tepid sponge compresses showed a significant decrease in temperature with an average difference of 1.2°C, while dry warm compresses only reduced the temperature by a difference of 0.2°C. Conclusion: Water tepid sponge compresses are more effective than dry warm compresses in reducing body temperature in children with fever at Pati Islamic Hospital.